A microtexture based analysis of surface roughening in ductile metals during tensile deformation - Wittridge, Nicola Janette (Centre for Materials Engineering, 2016)
This thesis examines the cause and mechanism for the occurrence of parallel surface ridges during the deformation of two specific ductile metal alloys, namely AISI 430 ferritic stainless steel and an aluminium alloy designated AA3002. The investigation considers, in particular, the development of parallel ridges during uniaxial tension, and their effect on the overall surface roughening of the sheet material. A detailed account of the microstructure and texture of the individual sample sheet materials is presented and proposals for the mechanisms of surface roughening are based on plasticity analysis of the actual material data. Both the microstructural characterisation and the texture determination was carried out using mainly electron microscopy techniques. Electron backscattered diffraction techniques were used to measure the microtexture, and analysis of this data allowed the calculation of the plastic flow behaviour of discrete volumes of the sample material. The yield behaviour was implemented in a finite element model to simulate the material behaviour under uniaxial tensile conditions. Analysis of microtexture results has indicated that elongated texture clusters are visible in the aluminium sample material which exhibits severe surface roughening during elongation in the rolling direction. It is proposed that initially surface roughening is the result of a variation in plastic flow of the surface grains due to the local texture clustering. With continued straining, the condition described by the MK analysis for strain localisation is able to arise and this leads to through-thickness strain localisation and necking, and so results in the formation of a ribbed profile. Ridging in stainless steel on the other hand can be attributed to an asymmetric distribution of texture components or plastic flow properties about the mid-plane of the material. An asymmetric arrangement yield properties initiates the development of differential transverse strains about the mid-plane of the material. The variation in transverse strain in turn results in a series of localised bending events which, on a macroscopic level, produces longitudinal corrugations and an overall ridged surface morphology.